Eskatologi : Keberadaan Alam Akhirat dalam Al-Qur'an: Kajian Tafsir Analitik (Tahlili) Surat Ibrahim Ayat 48 - Abdul Majid; Ainul Yaqin (Mahad Aly Al Fithrah, 2023)
Every soul in this world will die. After life in the world there is another life, namely life after die or afterlife. Afterlife always has been a mystery. Making imagination always imagined with various perceptions. The life of the world is the life that is currently taking.But between they both, there are things become problematic, namely the existence of world life and the afterlife, especially in regrading place. Where is the place of world? where is the place of hereafter? this is a questions that will be interesting to answer. For the existence of the life of the World, it is clearly the place on Earth as we have felt this during today. So what about the existence of the Hereafter itself? whether in other worlds, as understood by the majority of the people or perhaps the afterlife will also occur on this earth, because humans will be raised from their respective graves? This is where perhaps the talk of eschatology will result in the disclosure of the mystery of the mystery of the existence of the place of afterlife.